Effects of Coconut Sawdust on Mechanical Properties and Porosity of Concrete Mixtures - Edoardo E. Kumendong; Steve W.M. Supit; Helen Mantiri (Fakultas Teknik Universitas Sam Ratulangi, 2019)
The presence of coconut sawdust in North Sulawesi is very potential to be utilized as an alternative material for application in construction field. This paper aims to investigate experimentally the effect of coconut sawdust as an addition on concrete mixtures based on compressive strength, flexural strength and volume permeable voids tests. In this study, coconut sawdust with percentage of 2.5%, 5% and 7.5% by weight of cement was added into concrete mixture. The results show that concrete containing 5% of coconut sawdust exhibited highest compressive strength at 7 days with average value is 25.71 MPa while at 28 days the compressive strength is 30.50 MPa and there is no significant difference compared with 2.5% variation. When comparing the results of flexural strength test between 5% and normal cement concrete, the highest result is achieved by normal concrete reaching the value 6.78 MPa while for the concrete with 5% of coconut sawdust addition is only on 4.82 MPa. In terms of the volume of permeable voids, the results show that the porosity of concrete with coconut sawdust increased with the increase of percentage of coconut sawdust at 7 days but the values decreased as the age of curing increased.